2021
DOI: 10.3390/su131910627
|View full text |Cite
|
Sign up to set email alerts
|

Design Guideline for Flexible Industrial Buildings Integrating Industry 4.0 Parameters

Abstract: The emergence of Industry 4.0 can contribute to sustainable development, but most concepts have not yet received much attention in industrial building design. Industry 4.0 aims to realize production in batch size of one and product individualization on demand. Constant reconfiguration and expansion of production systems demand highly flexible building structures to prolong service life and reduce economic and environmental impacts. However, most research and tools focus on either production system or building … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…In order to extend the life cycle of industrial buildings, building structures must be able to adapt to reconfiguring and expanding production processes, which is a challenge for structural design. Optimizing the load-bearing structure for flexibility and coupling of production planning models already in the early design stage can contribute to increase the economic and environmental sustainability of industrial buildings [7,8]. Nonetheless, often, structural design decisions enter the industrial building design process late and are subservient to architectural and production goals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to extend the life cycle of industrial buildings, building structures must be able to adapt to reconfiguring and expanding production processes, which is a challenge for structural design. Optimizing the load-bearing structure for flexibility and coupling of production planning models already in the early design stage can contribute to increase the economic and environmental sustainability of industrial buildings [7,8]. Nonetheless, often, structural design decisions enter the industrial building design process late and are subservient to architectural and production goals.…”
Section: Introductionmentioning
confidence: 99%
“…The limited amount of research on flexibility in industrial buildings addresses the adaptive re-use of office and industrial buildings for residential purposes [27] and the flexible design of food processing [28] and biopharma facilities [29], or presents design guidance to support flexibility within architectural and engineering systems of factories [12]. Another study defines a categorized parameter catalogue as a design guideline for flexible industrial buildings that integrates production planning parameters [8]. However, the research conducted by Marjaba and Chidiac [30] has shown that there are no consistent metrics for evaluating the resilience and hence flexibility of industrial buildings in combination with sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research project BIMFlexi, a framework for integrated design of flexible industrial buildings is developed. In the context of the project, flexibility is defined as "the ability of the building structure to resist and adapt to changes in use through changing manufacturing conditions" (Reisinger et al, 2021a). Following this definition, the BIMFlexi design approach aims to create industrial building design solutions that can accommodate a variety of prioritized production plans.…”
Section: Introductionmentioning
confidence: 99%
“…Following this definition, the BIMFlexi design approach aims to create industrial building design solutions that can accommodate a variety of prioritized production plans. To achieve this goal, two major underlying problems in integrated industrial building design (Reisinger et al, 2021a) are addressed-1) lack of interoperability between discipline-specific tools and 2) poor communication workflows in the early design stage.…”
Section: Introductionmentioning
confidence: 99%